Environmental Science : A Global Concern - Cunningham William P; Cunningham, Mary Ann (New York : Mc-Graw Hill, 2012)
Environmental Science: A Global Concern, Twelfth Edition, is a comprehensive presentation of environmental science for non-science majors which emphasizes critical thinking, environmental responsibility, and global awareness. This book is intended for use in a one or two-semester course in environmental science, human ecology, or environmental studies at the college or advanced placement high school level. Cunningham and Cunningham have updated much of the data in the 12th edition; updated data on hunger and obesity, waste production, C02 emissions, and the effects of the 2010 oil spill are just a few examples. "Environmental Science: A Global Concern, Twelfth Edition", provides readers with an up-to-date, introductory global view of essential themes in environmental science. The authors balance evidence of serious environmental challenges with ideas about what we can do to overcome them. An entire chapter focuses on ecological restoration; one of the most important aspects of ecolog
Includes Index 596-613p.
Keywords: Biology; Environmental science; Environmental Biology